PENERAPAN MODEL GUIDED DISCOVERY LEARNING DALAM MENINGKATKAN PARTISIPASI BELAJAR SISWA SMKN 3 PONTIANAK - Riyanti, Mayang; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research is to know the use of guided discovery learning in improvingstudent participation on accountancy computer lesson on class XI in SMKN 3 Pontianak. The method in this research is the experimental method with pre-experimental design. The population in this research is 157 students. The number of samples in this research is 40 students. Data collection techniques in this research are direct communication techniques(interview guidelines), indirect communication techniques (student participation observation sheets), and documentary study techniques (photos of student learning activities). The results of this research showed that there is an increase in student participation before and after the experiment as many as 7.75. This can be known from the correlation value of both variables is 0.933 with a significance value 0.000, so that Ha is accepted. The conclusion of this research is that there is an increase in student learning participation after using guided discovery learning. Keywords: Guided Discovery Learning, Learning Participation